Self-Unity as Ground Zero of Learning and Development - Rochat, Philippe (Frontiers in Psychology, 2019)
Self-unity as Ground Zero of Learning and Development Abstract Contrary to the suggestion that we are born in a state of confusion and primordial state of a-dualism with the environment, infancy research of the past 40 years show that from the outset, infants are objective perceivers guided by rich evolved survival values of approach and avoidance in relation to specific resources in the environment such as faces, food, or smell. This innate competence drives and organizes their behavior. Evidence based ascription of self-unity at birth are discussed. Selected findings are presented suggesting that self-unity is a primordial human experience, the main organizer of behavior from the outset. Self-unity is the necessary ground zero enabling the rapid learning and development taking place early in human life.